2021
DOI: 10.3389/fnins.2021.687173
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture-Induced Muscular Inflammatory Pain Relief Was Associated With Activation of Low-Threshold Mechanoreceptor Neurons and Inhibition of Wide Dynamic Range Neurons in Spinal Dorsal Horn

Abstract: Acupuncture is an effective alternative therapy for pain management. Evidence suggests that acupuncture relieves pain by exciting somatic afferent nerve fibers. However, the mechanism underlying the interaction between neurons in different layers of the spinal dorsal horn induced by electroacupuncture (EA) remains unclear. The aim of this study was to explore the mechanism of EA relieving inflammatory muscle pain, which was associated with activation of the spontaneous firing of low-threshold mechanoreceptor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…44 In addition, the underlying mechanisms of the segmental analgesia of acupuncture have been suggested to be associated with the gate control theory. 10,16,45 In this study, pre-EA with low intensity T Aβ inhibited nociceptive discharges of WDR neurons, indicating that anti-nociceptive effects of pre-EA may also be related to the gate control theory. However, the phenomena only occurred when pre-EA with T Aβ was administered at adjacent non-RFs.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…44 In addition, the underlying mechanisms of the segmental analgesia of acupuncture have been suggested to be associated with the gate control theory. 10,16,45 In this study, pre-EA with low intensity T Aβ inhibited nociceptive discharges of WDR neurons, indicating that anti-nociceptive effects of pre-EA may also be related to the gate control theory. However, the phenomena only occurred when pre-EA with T Aβ was administered at adjacent non-RFs.…”
Section: Discussionsupporting
confidence: 52%
“…Previous studies determined the intensity of EA by recordings of nociceptive reflexes (RIII reflex). 10,11,16 As the C-fiber reflex was a kind of nociceptive response, 59,60 it was difficult to find out the threshold of Aβ-fiber. Other studies employed single-unit recording of primary afferent fibers or sensory neurons to determine the intensity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in inflammatory muscle pain rats, low-strength electroacupuncture (EA) has been shown to reduce the introduction of pain information through the spinal gate-control mechanism, significantly alleviating pain and inhibiting the abnormal electromyography. 7 Previous studies have also demonstrated that heterotopic EA stimulation triggers the pain-inhibiting effect of diffuse noxious inhibitory controls (DNICs). 15 In addition, Han 9 found that acupuncture applied at specific frequencies to certain body sites can stimulate the release of endogenous opioid peptides in the central nervous system and activate opioid receptors to induce antinociception.…”
Section: Introductionmentioning
confidence: 99%